Experiences of mothers and female community health workers accessing and implementing the Marwo Caafimaad programme in Somalia - Ayan Mohamed; Kathleen West; James Pfeiffer; Ahmed Ali; Farah Mohamed; Mohamed Ali; Abdirizak Hersi; Abdirisak Artan; Isse Jama; Salma Osman (Eastern Mediterranean Health Journal, 2026)
Background: Somalia has one of the highest maternal mortality ratios globally, with low antenatal care coverage and low skilled birth attendance. In Puntland, Somalia, the Marwo Caafimaad programme trains female community health workers to provide reproductive health education, basic care and referrals. Aim: To assess the experiences of mothers and female community health workers accessing and implementing the Marwo Caafimaad programme in Puntland, Somalia. Methods: In 2022, we conducted focus group discussions with 45 eligible mothers accessing services through the Marwo Caafimaad programme in 7 villages of Puntland, Somalia, and in-depth interviews with 9 community health workers involved in implementing the programme. We analysed the data thematically using Dedoose version 9.0.107. Results: The mothers valued the programme for providing trusted, home-based support and reducing barriers to care related to distance, cost and family responsibilities. Female community health workers reported strong community acceptance and supportive supervision of the programme. Both groups identified lack of local maternal and child health care centres, shortage of medicines and supplies, inadequate staffing, limited refresher training, and delayed or insufficient remuneration as barriers limiting programme impact. Conclusion: The services provided by Marwo Caafimaad were highly valued in the remote communities of Puntland, however, resource and workforce constraints limited the impact of these services. Additional investment in local facilities, supplies, remuneration, workforce expansion, and training is needed to strengthen the programme.